SOCIO-LEGAL FOUNDATIONS OF RELIGIOUS EDUCATION IN OUR COUNTRY - Firuz Tuygunovich Rashidov (Web of Journals Publishing, 2024)
This article focuses on the concept of education in the Republic of Uzbekistan, the concept of religious and secular education, the right and basis of education, opportunities for religious education, the analysis of the legal framework of religious and secular education, as well as activities in the field of religious education.
Keywords: Education, science, knowledge, religious education, religious values, combination of secular and religious education, continuing education, compulsory education, denomination, qualified personnel.